Dynamic soaring as a means to exceed the solar wind speed - Larrouturou, Mathias N.; Higgins, Andrew J.; Greason, Jeffrey K. (Frontiers in Space Technologies, 2022)
A technique by which a spacecraft can interact with flows of ionized gas in space (the solar wind or interstellar medium) in order to be accelerated to velocities greater than the flow velocity is explored. Inspired by the dynamic soaring maneuvers performed by sea birds and gliders in which differences in wind speed are exploited to gain velocity, in the proposed technique a lift-generating spacecraft circles between regions of the heliosphere that have different wind speeds, gaining energy in the process without the use of propellant and only modest onboard power requirements. In the simplest analysis, the spacecraft motion can be modeled as a series of elastic collisions between regions of the medium moving at different speeds. More detailed models of the spacecraft trajectory are developed to predict the potential velocity gains and the maximum velocity that may be achieved in terms of the lift-to-drag ratio of the vehicle. A lift-generating mechanism is proposed in which power is extracted from the flow over the vehicle in the flight direction and then used to accelerate the surrounding medium in the transverse direction, generating lift (i.e., a force perpendicular to the flow). Large values of lift-to-drag ratio are shown to be possible in the case where a small transverse velocity is imparted over a large area of interaction. The requirement for a large interaction area in the extremely low density of the heliosphere precludes the use of a physical wing, but the use of plasma waves generated by a compact, directional antenna to impart momentum on the surrounding medium is feasible, with the excitation of R-waves, X-waves, Alfven waves, and magnetosonic waves appearing as promising candidates. A conceptual mission is defined in which dynamic soaring is performed on the termination shock of the heliosphere, enabling a spacecraft to reach speeds approaching 2% of c within two and a half years of launch without the expenditure of propellant. The technique may comprise the first stage for a multistage mission to achieve true interstellar flight to other solar systems.